2019
DOI: 10.1093/hropen/hoz008
|View full text |Cite
|
Sign up to set email alerts
|

Required amount of rFSH, HP-hMG and HP-FSH to reach a live birth: a systematic review and meta-analysis

Abstract: STUDY QUESTION In women undergoing IVF or ICSI cycles, do recombinant gonadotrophins differ from urinary-derived highly purified human menopausal gonadotropin (HP-hMG) or highly purified follicle-stimulating hormone (HP-FSH) in the total amount of gonadotrophins required to reach a live birth? SUMMARY ANSWER The difference between recombinant and urinary-derived HP-hMG or HP-FSH in the required amount to reach a live birth in IVF/ICSI cycles appears small. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
4
23
1
Order By: Relevance
“…Our findings are in accordance to previous clinical randomized trials that compared rFSH and hMG in GnRH antagonist cycles ( Bordewijk et al , 2019 ; Bosch et al , 2008 ). They observed a lower number of oocytes retrieved with a mean difference of 3.1 in favor of the hMG group, and a lower number of MII oocytes with a mean difference of 1.9.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in accordance to previous clinical randomized trials that compared rFSH and hMG in GnRH antagonist cycles ( Bordewijk et al , 2019 ; Bosch et al , 2008 ). They observed a lower number of oocytes retrieved with a mean difference of 3.1 in favor of the hMG group, and a lower number of MII oocytes with a mean difference of 1.9.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have compared rFSH and hMG in IVF cycles regarding their effectiveness in ovarian stimulation. Since hMG has a different composition, concerning the presence of LH, it has been speculated that this would affect the outcomes in follicular recruitment, follicular growth, number and quality of embryos and pregnancy rates ( Bordewijk et al , 2019 ; Zeleznik & Kubik, 1986 ; Ziebe et al , 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…21 In ET recipients, in addition to spontaneous contractions, the uterus is exposed to strong contractile stimuli arising from the transcervical passage of the transfer catheter and, in some cases, from using a tenaculum. 5,6 To achieve maximal relaxation of the uterus during ET, it is advised to perform ET gently, without excessive stimulation of the cervix. Other methods to inhibit excessive uterine contractions include lowering patient stress and using a myorelaxant, acupuncture, or an oxytocin antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo transfer (ET) has been recognized as a vital step that influences pregnancy rates in patients undergoing in vitro fertilization (IVF). 1,2 To date, however, other stages of IVF have received more attention than ET, such as nutrition supplementation, 3,4 ovarian stimulation, 5,6 embryo incubation conditions, 7,8 endometrial scratching, 9,10 and luteal phase support. 11,12 Undoubtedly, the safe placement of embryos in the uterine cavity is essential to obtaining an optimal pregnancy rate, but there is no guarantee that embryos will remain in the uterine cavity after the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data from animal models showed that the currently available r-hFSH medications have no teratogenic, mutagenic or clastogenic effects, an evidence that was further supported by a series of trials and meta-analysis regarding the safety and effectiveness of r-hFSH for women undergoing IVF [ 16 , 27 , 28 , 29 ], including poor responder patients of advanced age and women with polycystic ovary syndrome (PCOS) [ 30 ]. Pharmacokinetic studies showed that r-hFSH is no more detectable in the woman’s blood by the time of embryo implantation, and no detrimental effects on the fetus after accidental exposure to r-hFSH in early pregnancy have been reported; moreover, r-hFSH is not believed to increase the risk of abortion or affect birthweight [ 31 ].…”
Section: Recombinant Human Fsh (R-hfsh)mentioning
confidence: 99%